Healing and leishmanicidal activity of Zanthoxylum rhoifolium Lam. - Correa-Barbosa, Juliana; Brígido, Heliton Patrick Cordovil; Matte, Bibiana Franzen; Campos, Paloma Santos De; Lamers, Marcelo Lazzaron; Sodré, Daniele Ferreira; Nascimento, Pedro Henrique Costa; Ferreira, Gleison Gonçalves; Vale, Valdicley Vieira; Marinho, Andrey Moacir do Rosário; Siqueira, José Edson De Sousa; Coelho-Ferreira, Márlia Regina; et al. (Frontiers in Chemistry, 2025)
Zanthoxylum rhoifolium is used in folk medicine as an antiparasitic agent. Therefore, this study evaluated the phytochemical aspects and biological activities of Z. rhoifolium. For this, the ethanolic extract (EE) was obtained by macerating the peel with ethanol and subjected to acid-base partition to obtain the neutral fractions (FN) and alkaloid fractions (FA). These samples were analyzed using chromatography techniques. From this, a substance was isolated from FN and identified by nuclear magnetic resonance. For biological activity, strains of Leishmania amazonensis were used for leishmanicidal activity. For cytotoxicity, cell viability methods were used and finally, the selectivity index (SI) was determined. Cell proliferation assay (SRB method) was also performed, such as a wound healing assay. After analysis, it was inferred that in chromatography, EE, FN and FA presented peaks suggestive of alkaloids, and the alkaloid chelerythrine was isolated from FN. In antiparasitic activity against promastigotes, EE, FN and FA were active. Against amastigotes, the infection inhibition index was dose dependent for EE and FN. In the cytotoxicity test (J774), EE and FN showed moderate cytotoxicity, while FA demonstrated cytotoxicity. In VERO strain, EE and FA showed moderate cytotoxicity, while FN was not cytotoxic. Finally, considering the SI, EE, FN and FA showed high selectivity. Furthermore, EE and FN increased cell proliferation and FN promoted a healing effect. Thus, it is highlighted that the specie Z. rhoifolium presented antileishmanial activity and selectivity for the parasite, and its FN presented healing potential.